Listeriosis Cases and Genetic Diversity of Their L. monocytogenes Isolates in China, 2008–2019 - Lu, Binghuai; Yang, Junwen; Gao, Chunyan; Li, Dong; Cui, Yanchao; Huang, Lei; Chen, Xingchun; Wang, Duochun; Wang, Aiping; Liu, Yulei; Li, Yi; Zhang, Zhijun; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Listeriosis, caused by Listeria monocytogenes, is a severe food-borne infection. The nationwide surveillance in China concerning listeriosis is urgently needed. In the present study, 144 L. monocytogenes isolates were collected from the samples of blood, cerebrospinal fluid (CSF), and fetal membrane/placenta in China for 12 years from 2008 to 2019. We summarized these listeriosis patients’ demographical and clinical features and outcomes. The susceptibility profile for 12 antibiotics was also determined by the broth microdilution method. Multilocus sequence typing (MLST) and serogroups of these listeria isolates were analyzed to designate epidemiological types. We enrolled 144 cases from 29 healthcare centers, including 96 maternal-neonatal infections, 33 cases of bacteremia, 13 cases of neurolisteriosis, and 2 cutaneous listeriosis. There were 31 (59.6%) fetal loss in 52 pregnant women and 4 (9.8%) neonatal death in 41 newborns. Among the 48 nonmaternal-neonatal cases, 12.5% (6/48) died, 41.7% (20/48) were female, and 64.6% (31/48) occurred in those with significant comorbidities. By MLST, the strains were distinguished into 23 individual sequence types (STs). The most prevalent ST was ST87 (49 isolates, 34.0%), followed by ST1 (18, 12.5%), ST8 (10, 6.9%), ST619 (9, 6.3%), ST7 (7, 4.9%) and ST3 (7, 4.9%). Furthermore, all L. monocytogenes isolates were uniformly susceptible to penicillin, ampicillin, and meropenem. In summary, our study highlights a high genotypic diversity of L. monocytogenes strains causing clinical listeriosis in China. Furthermore, a high prevalence of ST87 and ST1 in the listeriosis should be noted.